การพัฒนาทักษะการรู้เท่าทันสื่อเพื่อป้องกันการตกเป็นเหยื่อทางเพศและกลยุทธ์การจัดการท่ามกลางนักศึกษามหาวิทยาลัย - ฤทัยชนนี สิทธิชัย (มหาวิทยาลัยสงขลานครินทร์, 2025)
This mixed-methods study investigated sexting and related victimization and coping strategies among 18-24 year-old university students in Southern Thailand. The data were collected with an online survey of 1378 students and telephone interviews with 18 students. Descriptive statistics are reported and a content analysis of the interviews was conducted. When asked about sexting frequency, 25% of the surveyed students indicated they had received sexts from their boy/girlfriend, 22% had sent sexts, and 38% had received sexts forwarded by others. Older, male, transgender, and nonbinary students had relatively higher sexting prevalence rates. We found no systematic differences in sexting between Buddhist and Islamic students. Interviews indicated that many students shared sexy or pornographic contents with friends rather than with partners. Twitter, Facebook, and LINE were key sexting platforms. Over a third of male and female students agreed that when sexting occurs, bad things happen. All interview participants had experienced online, sexuality-related victimization. For the interview participants these consisted of online sexual harassment (unwanted explicit photos, videos, messages, & calls) and impersonation, which can be considered a form of cyberbullying. While the interview participants did not share experiences of having their explicit photos or videos leaked publicly, many contributed to the victimization of others by forwarding leaked, explicit photos and videos of other people. Our interviews indicated that while experiences of online sexuality-related victimization impacted both female and male students emotionally, many simply tried to stop thinking about it. When victimized, many talked with their friends (if with anyone), but hardly any talked with their parents, instructors, or reported the incident to the police. Only six of the 18 interview participants could name a relevant law (the Computer Crime Act), and all but one thought it had limited usefulness in dealing with the victimization they experienced. Many students used technological means to prevent further victimization (blocking & reporting). In the survey, 55% had never had discussions about sexting as a part of a university lesson. When the interview participants were asked where they could find relevant information, they largely sought it online on the same platforms where victimization also occurred. Overall, our findings suggest that educational institutions are not doing enough to prevent sexting-related victimization or other forms of online sexual victimization such as online sexual harassment or sexuality-related cyberbullying.